Screening for Thermoactinomyces vulgaris in Fermented Grains of Sauce-Flavor Baijiu and Metabolic Analysis of Volatile Compounds - ZHAI Weitao, WU Shuangquan, CHAI Lijuan, LU Zhenming, ZHANG Xiaojuan, YANG Yang, YU Hui, YE Qingqing, TIAN Maoling, LIU Xiaotong, MAO Xueting, WANG Songtao, SHEN Caihong, XU Zhenghong (Shipin Kexue)
In order to screen for potential Thermoactinomyces from stacked fermented grains of sauce-flavor baijiu, three strains of Thermoactinomyces valgaris were obtained by enrichment and isolation and identified by morphology and molecular biology. The metabolic characteristics of volatile compounds produced in liquid-state fermentation by each strain were investigated. Additionally, solid-state fermentation experiments were performed at 45 or 50 ℃. The flavor metabolism profiles of each strain at different fermentation stages were analyzed and summarized under liquid-state and solid-state fermentation conditions. The results showed that all three T. vulgaris strains grew rapidly in the liquid medium. They entered the logarithmic growth phase between 10 and 16 h and attained the stationary phase at 34 h, and the accumulation of acidic substances and pyrazines was enhanced. Specifically, strain ts5 displayed the highest concentrations of 2-methyl butyric acid and 2,3,5-trimethylpyrazine, amounting to 4.14 and 0.72 mg/L, respectively. The total quantity of volatile compounds produced in solid-state fermentation gradually ascended over the fermentation period. Notably, solid-state fermentation at 50 ℃ enabled a more substantial accumulation of flavor compounds such as esters, phenols, and pyrazines in comparison with that at 45 ℃. Collectively, the aroma production of T. vulgaris in solid-state fermentation on Hongyingzi sorghum was superior to that in liquid-state fermentation. Moreover, fermentation at 50 ℃ was more conducive to the accumulation of flavor compounds when compared with 45 ℃. The results of this study provide a theoretical basis for understanding the aroma-producing performance of T. vulgaris during high-temperature stacking fermentation.